Systematic Review of Reading Skills in 7-8-Year-Old Children - Sukmakarti, Laksmy Dewi; Muryanti, Muryanti; Siswanto, Arif (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Reading ability in children aged 7-8 years is a critical foundation for academic and cognitive development. However, data indicates that 60% of Indonesian 2nd-grade students lack optimal reading fluency, facing challenges such as phonological difficulties, sentence structure comprehension, and limited literacy stimulation at home. Objectives: This study aims to analyze factors influencing reading ability in children aged 7-8 and identify effective remediation strategies. Methods: A systematic review was conducted, analyzing 5 selected articles from Google Scholar (2020–2025) using keywords related to reading fluency and school-age children. Results: Findings revealed that reading difficulties stem from internal (motivation, phonological awareness) and external factors (parental involvement, book access). Multisensory interventions, parental guidance, and balanced literacy methods significantly improved reading skills. Conclusion: Enhancing reading ability requires collaborative efforts among schools, families, and policies promoting inclusive literacy access. Keywords : School-age children, Reading ability, Reading fluency